Impact of full-scale models on students’ creativity in basic design course - Elaby, Mohammed; Mohamed, Hany; Wafa, Mohamed; Sweilam, Sayed (Creativity Studies, 2023)
Designing and implementing full-scale models by architecture students is one of the most difficult and uncommon experiences in design education. The study evaluates the impact of this experience on the development of creative design skills among first-year students. This is achieved by applying a methodology that combines quantitative analysis of learning outcomes, especially those associated with the skills of Basic Design courses, with qualitative analysis of sketches, scaled and full models, and video recordings of students during design and implementation stages. This study provides experimental support for the use of full-scale models in design education to develop students’ creative skills, in addition to discussing opportunities and challenges to help faculty and researchers in the field of design education.